Erythrocyte Sedimentation and Soluble Fibrin Monomer Complexes - Lipiński, B; Worowski, K; Myśliwiec, M; Farbiszewski, R (Thrombosis and Haemostasis, 1969)
It is shown in the present work that highly significant correlation (r = 0.836) exists between the level of SFMC and the erythrocyte sedimentation rate in blood of 56 patients. No correlation of ESR with fibrinogen content was observed in 1 patient during the post-operative period, as well as in the group of experimentally infected rabbits. Administration of fibrinolysis inhibitors into rabbits (EACA, IP-315, HgCl2) caused in all cases a significant increase in ESR and in plasma SFMC with unrelated elevation of the fibrinogen level. Protamine sulphate added to whole blood with high ESR to final concentration 1 mg/ml of blood completely abolished the sedimentation of erythrocytes. A hypothesis is formulated according to which red cells interacting with SFMC increase their sedimentation rate.